PERAN HOT AIR GUN DALAM PROSES PERBAIKAN PRODUK BOX ES UNTUK MENUNJANG KUALITAS PRODUKSI DI PT HARMONY PILAR SENTOSA - nabil makarim nabil; Ilham Pahlawan (ENIGMA: Engineering in Green Machinery, 2026)
This study aims to describe the role of the Hot Air Gun in the repair process of ice box products as an effort to improve production quality at PT Harmony Pilar Sentosa. The Hot Air Gun is used as the main tool in the plastic welding method for thermoplastic materials, especially for repairing damage such as porosity, leakage, and defects on the plug and flange areas. This research uses a descriptive qualitative method with data collected through field observation, interviews, and documentation of the welding process. The results show that the use of the Hot Air Gun can increase joint strength, improve surface structure, and restore the function of the ice box according to production standards. Field identification indicates an average defect of 900–1000 units per month, with the dominant defects being porosity on the flange and surface scratches. The repair process using the Hot Air Gun is proven to minimize rejected products and improve production efficiency. In addition, visual and mechanical testing shows that the welding results provide strong, neat, and leak-resistant joints. These findings confirm that the use of the Hot Air Gun is an effective technical solution to support improved production quality and repair process efficiency.